TI_GERICHTE 52.2020.7 vom 18. Dezember 2019 , Revoca della licenza di condurre cautelativa. Restituzione in intero - TI Tribunale d'appello (2019)
Revoca della licenza di condurre cautelativa. Restituzione in intero